The Role of the IAIN Kerinci Internship Team in the Religious Data Collection Process in the Sitinjau Laut Subdistrict of Kerinci Regency - Uswatun Hasanah; Jamal Mirdad; Auliani Eka Putri (Jurnal Masyarakat Religius dan Berwawasan, 2023)
The purpose of this study was to analyze the religious community through the facilities and infrastructure of worship and religious programs in the District of  Sitinjau Laut Kerinci regency. In the process of religious data collection is currently carried out manually both religious information and other information in each village. The problem is that there are many data input errors that require repeated data collection by the team and require a long registration process. To that end, the team tried to re-record the data in the community. The research method used in this study is field research, ie. observations, interviews and research literature. DFD (Data Flow Diagram), ERD (Entity Relationship Diagram) and Data Dictionary are also used in system planning. The results showed that the community in the District of Sitinjau Sea using the means of worship effectively with some religious programs and Islamic education. With the existence of adequate facilities can increase the religious community, because the more effective the means of worship functioned, the more increased the religious community.